The Effect of Using Quizizz as an Evaluation Medium on the Learning Progress of Informatics Students in Class X - Sovia Sovia; Vera Irma Delianti; Elfi Tasrif; Delvi Asmara (Universitas Ibn Khaldun, 2025)
This study aims to analyze the effect of using Quizizz as an evaluation medium on the learning progress of tenth-grade Informatics students at SMAN 1 Gunuang Omeh. The research employed a quantitative approach with a quasi-experimental design using two classes: one experimental class utilizing Quizizz for formative assessment and one control class using conventional paper-based tests. Data were collected through pretests and posttests to measure students’ progress before and after treatment. Statistical analyses included normality, homogeneity, and independent samples t-tests. The results showed that the average posttest score of the experimental class (86.81) was higher than that of the control class (79.74). The t-test value of -2.841 with a significance level of 0.006 (<0.05) indicated a significant difference between the two groups. These findings demonstrate that the use of Quizizz as an evaluation medium significantly improves students’ learning progress by fostering engagement, motivation, and immediate feedback. The integration of technology-based evaluation enhances interactivity and helps students better understand learning materials. Thus, Quizizz proves to be an effective alternative evaluation tool for supporting meaningful and enjoyable learning experiences in Informatics education.